Triterpenoid-PEG Ribbons Targeting Selectivity in Pharmacological Effects - Özdemir, Zulal; Bildziukevich, Uladzimir; Čapková, Martina; Lovecká, Petra; Rárová, Lucie; Šaman, David; Zgarbová, Michala; Lapuníková, Barbora; Weber, Jan; Kazakova, Oxana; Wimmer, Zdeněk (Biomedicines, 2021)
(1) Background: To compare the effect of selected triterpenoids with their structurally resembling derivatives, designing of the molecular ribbons was targeted to develop compounds with selectivity in their pharmacological effects. (2) Methods: In the synthetic procedures, Huisgen 1,3-dipolar cycloaddition was applied as a key synthetic step for introducing a 1,2,3-triazole ring as a part of a junction unit in the molecular ribbons. (3) Results: The antimicrobial activity, antiviral activity, and cytotoxicity of the prepared compounds were studied. Most of the molecular ribbons showed antimicrobial activity, especially on Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecalis, with a 50-90% inhibition effect (c = 25 µg·mL-1). No target compound was effective against HSV-1, but 8a displayed activity against HIV-1 (EC50 = 50.6 ± 7.8 µM). Cytotoxicity was tested on several cancer cell lines, and 6d showed cytotoxicity in the malignant melanoma cancer cell line (G-361; IC50 = 20.0 ± 0.6 µM). Physicochemical characteristics of the prepared compounds were investigated, namely a formation of supramolecular gels and a self-assembly potential in general, with positive results achieved with several target compounds. (4) Conclusions: Several compounds of a series of triterpenoid molecular ribbons showed better pharmacological profiles than the parent compounds and displayed certain selectivity in their effects.
Keywords: anti-HIV activity; molecular ribbon; antimicrobial activity; cytotoxicity; supramolecular self-assembly; triterpenoid; multifunctional PEG3 derivative; Huisgen 1,3-dipolar cycloaddition; amide bond